2019
DOI: 10.12717/dr.2019.23.1.035
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of Growth Related Genes in Juvenile Red Spotted Grouper (Epinephelus akaara) with Different Growth Performance after Size Grading

Abstract: Fish shows great difference in growth rate between individuals during larval development and early growth. This difference seriously reduces the production efficiency in fish culture. Growth hormone (GH)/Insulin-like growth factor 1 (IGF1) system is said to play some pivotal roles in fish growth. In this study, we investigated differences of GH, IGF1 and GHR gene expressions in juvenile red spotted grouper ( Epinephelus akaara ) with different growth performance. Red spotted groupers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Growth rate was improved by 15% and 12% in the grading every two weeks and grading every four weeks over the control group. This is in agreement with previous studies that have established that size grading affect the growth performance of several species of fish (Barki et al, 2000;Kamstra, 1993;Lambert & Dutil, 2001;Mgaya & Mercer, 1995;Mun et al, 2019;Nightingale et al, 2018). In restricted spaces such as ponds, aquaria and concrete tanks, the African catfish tends to exhibit changes in behavioural patterns when there are size variations in the cohorts leading to reduced feed intake, aggression, death and cannibalism (Martins et al, 2005b).…”
Section: Discussionsupporting
confidence: 92%
“…Growth rate was improved by 15% and 12% in the grading every two weeks and grading every four weeks over the control group. This is in agreement with previous studies that have established that size grading affect the growth performance of several species of fish (Barki et al, 2000;Kamstra, 1993;Lambert & Dutil, 2001;Mgaya & Mercer, 1995;Mun et al, 2019;Nightingale et al, 2018). In restricted spaces such as ponds, aquaria and concrete tanks, the African catfish tends to exhibit changes in behavioural patterns when there are size variations in the cohorts leading to reduced feed intake, aggression, death and cannibalism (Martins et al, 2005b).…”
Section: Discussionsupporting
confidence: 92%
“…indicated that the growth hormone (GH)/insulin‐like growth factor 1 (IGF1) was highly expressed in the fast‐growing (FG) juvenile of red spotted grouper ( Epinephelus akaara ), especially in the muscle tissue, compared with the slow‐growing (SG) breed (Mun et al ., 2019). Nonetheless, these growth‐related genes are widely distributed in both FG and SG fish, with only limited genetic variations, making the selection of genetic markers difficult (Mun et al ., 2019; Reis Neto et al ., 2019). Recent transcriptomic studies have shown that there are considerable differences in the expression patterns of these genes between FG and SG breeds, especially those associated with hormone and lipid metabolism (Cleveland et al ., 2020; Lu, Chen, et al ., 2020; Mun et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these growth‐related genes are widely distributed in both FG and SG fish, with only limited genetic variations, making the selection of genetic markers difficult (Mun et al ., 2019; Reis Neto et al ., 2019). Recent transcriptomic studies have shown that there are considerable differences in the expression patterns of these genes between FG and SG breeds, especially those associated with hormone and lipid metabolism (Cleveland et al ., 2020; Lu, Chen, et al ., 2020; Mun et al ., 2019). Overall, these findings improve the understanding of the molecular mechanisms of growth, providing target genes and markers to increase the efficiency of selective breeding (Yang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In fish, AMPK is reported to maintain cellular energy and promotes catabolic pathways to provide energy (Causey et al, 2019;Sanchez-Gurmaches et al, 2012). The expression of these genes has been reported to be related to the better growth rate in several fish species (Gilannejad et al, 2020;Mun et al, 2019). Aside from its expression levels, the polymorphisms of growth-related genes such as GH and IGF-1 gene were also reported to be related to the better growth in fish such as in common carp (Berenjkar et al, 2018), Atlantic salmon (Tsai et al, 2014), and Chinese perch (Tian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%